Challenges of sustainable food technology a review - Tolnay Anita; Nath Arijit; Kőris András (University of Szeged, Faculty of Engineering, 2020)
Over the last decades due to rapid development of human civilization along with revolution in technology, some burning issues about generation of environmental contaminant, management of by-products from technologies, high consumption of natural resources and conservation of natural resources have been dramatically raised. Without any contradiction, impacts in overall ecosystem as well as human civilization have negative effects. These evoked lots of scientific and industrial researches, and implemented several stricter environmental legislations on the development of sustainable ecosystem. Thus, sustainability has become an emerging topic all over the world, as evidenced by the growing body of scientific publications in the last 20 years with one order of magnitude increase since the start of the new century. The study attempts to perform a review of the sustainable development from the food industry’s perspective. At present, the agro-food sector produces high amount of carbon dioxide, food waste, packaging waste, wastewater, etc. and it is still consuming a lot of water, land, oxygen and energy. Furthermore, taken into consideration the increasing number of the world’s population, there has been an enhancing interest experienced towards sustainable development among food manufacturers in the last decades. The article highlights the paramount areas of sustainable production, which offers new directions towards the increasing number of human beings for the future survival. The paper also gives an overview of the main perspectives contra constraints of sustainable food production, offers innovative food products from sustainable food waste and by-product, and focuses on the growing importance of sustainable food production in life cycle assessment methodology as well.
Keywords: Műszaki és technológiai tudományok